Qingping Straight Sword: The Last Remaining Chinese Sword System? (Revista de Artes Marciales Asiáticas, 2012)
The following examination of classical Chinese straight sword (jian) details the very rare Qingping straight sword system. The study meshes Chinese- and English-sourced research with a revealing interview (conducted by America’s senior Qingping disciples, Reza Momenan and Hon Lee) with Lu Junhai—the grandmaster of this unique sword system. The author presents Qingping system as perhaps the only known, complete Chinese sword system surviving from China’s pre-Rebulican era (1911-1949).